2020
DOI: 10.3390/ma13122742
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and Transformation of Vaterite Calcium Carbonate in the Presence of Some Organic Solvents

Abstract: In this paper, the production of CaCO3 particles via the carbonation route in the reaction of CaCl2 and CO2, using NH3 as a promoter of CO2 absorption, was studied. The solvents used as the reaction media for CaCO3 precipitation were aqueous solutions of methanol, isopropanol and dimethyl sulfoxide (DMSO), in a concentration range of 0–20% (v/v). It was found that the presence of an organic additive influenced the precipitation rate, the content of vaterite in the obtained product, the morphology and the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…This suggests that during the post functionalization using HMDS and toluene at 80 °C, some CaCl 2 phases already present in the SBA-15 might have transformed to CaCO 3 via a carbonation route. 40 XRD of COO − functionalized SCa4 exhibited both CaCl 2 •2H 2 O and CaCl 2 •4H 2 O phases suggesting the presence of large crystalline CaCl 2 particles in this composite that are outside the silica mesopores (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that during the post functionalization using HMDS and toluene at 80 °C, some CaCl 2 phases already present in the SBA-15 might have transformed to CaCO 3 via a carbonation route. 40 XRD of COO − functionalized SCa4 exhibited both CaCl 2 •2H 2 O and CaCl 2 •4H 2 O phases suggesting the presence of large crystalline CaCl 2 particles in this composite that are outside the silica mesopores (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…CaCl 2 phases already present in the SBA-15 might have transformed to CaCO 3 via carbonation route 40. XRD of COOfunctionalized SCa4 exhibited both CaCl 2 .2H 2 O and CaCl 2 .4H 2 O phases…”
mentioning
confidence: 97%
“…It was reported that the change in polymorph from calcite to vaterite and aragonite formation occurred at 40 ℃. The different report stated by Song et al, (2020) that the vaterite phase changes to calcite with an increase in temperature from 20 to 80 ° C. The vaterite formation observed at 60 ℃ (Konopacka-Łyskawa et al, 2020). Polymorph aragonite is the dominant species at high temperatures (Ramakrishna et al, 2017) due to higher growth rates of aragonite as compared to the other polymorphs (Chong et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…CaCO3 was difficult in controlling its polymorphic character (Chong et al, 2014). Several factors affect the precipitation process and polymorph characteristics such as pH (Thriveni et al, 2016;Tobler et al, 2016), supersaturation (Ding et al, 2018), temperature (Chong et al, 2014), calcium source (Bang et al, 2015), precipitation method (Thriveni et al, 2016), mixing intensity (Ševčík, et al, 2015) and co-solvent type (Konopacka-Łyskawa et al, 2020). Organic additives affected the rate of precipitation and the morphology of the precipitated particles (Polat, 2020;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[21,[26][27][28][29] One of the main drawbacks of vaterite crystals are their inherent metastability and rather quick degradation/recrystallization in aqueous environments. [30] Degradation/decomposition of vaterite is required for hard templating of polymer, protein, inorganic or hybrid structures [22,[31][32][33][34] by means of loading the vaterite pores, followed by vaterite solubilisation. Although such properties may be beneficial for some medical applications, for example, pH-triggered release in tumor sites, [35][36][37] many other applications require the stabilization of vaterite and the suppression of its recrystallization.…”
Section: Introductionmentioning
confidence: 99%